Effects of holistic nursing interventions in newborns with hypoxic-ischemic encephalopathy (缺氧缺血性脑病新生儿整体护理效果观察) - HE Xuelian (何雪莲); WANG Jing (王京); LIU Li (刘丽) (中西医结合护理)
Objective To investigate the effect of holistic nursing interventions in newborns with hypoxic-ischemic encephalopathy. Methods Totally 60 newborns with hypoxic-ischemic encephalopathy were recruited as research objects. Based on the basic treatment of hypoxic-ischemic encephalopathy, all newborns received hyperbaric oxygen therapy and holistic nursing interventions. The partial pressure of oxygen and oxyhemoglobin saturation of newborns were recorded, and score of Neonatal Behavioral Neurological Assessment (NBNA) were compared before and after treatment. Results The partial pressure of oxygen and oxyhemoglobin saturation of newborns were effectively improved after intervention. The total score of NBNA and each dimensional score after intervention were significantly higher than those before intervention (P＜0. 05). Conclusion Based on the basic treatment of hypoxic-ischemic encephalopathy, the holistic nursing interventions are effective to improve the treatment efficacy and behavioral ability of newborns. (目的 探讨整体护理在缺氧缺血性脑病新生儿护理中的应用效果。方法 选取60例缺氧缺血性脑病患儿为研究对象。在缺氧缺血性脑病基础治疗的基础上给予高压氧治疗, 同时配合整体护理方案。记录患儿氧分压和血氧饱和度, 观察患儿行为神经测定(NBHA)评分。结果 干预后患儿氧分压和血氧饱和度得到有效改善。患儿NBHA量表总分及各维度评分较干预前提高, 差异有统计学意义(P＜0. 05)。结论 在对缺血缺氧性脑病患儿护理中实施整体护理方案, 能确保治疗效果, 有效改善行为神经发育。)